Multiple Thermal Gelation of Hydroxypropyl Methylcellulose and Kappa-Carrageenan Solutions and their Interaction with Salts - Almeida, Nalinda; Rakesh, Leela; Zhao, Jin (Journal of Composites and Biodegradable Polymers, 2017)
The multiple gelation behavior of aqueous solutions of kappa-carrageenan (KCG) and low molecular weight hydroxypropyl methylcellulose (HPMC) was studied with the presence of various salts. Multiple gelation behavior of aqueous solutions of HPMC/KCG/salt mixture were found. The shear viscosity of HPMC/KCG blend increased by one orders of magnitude, while the viscosity of HPMC/KCG/potassium chloride (KCl) mixture increased by three orders of magnitude as compared to HPMC solution at temperatures below apparent gelation. The dynamic elastic modulus of HPMC/KCG blend increased by two orders of magnitude, while the elastic modulus of HPMC/KCG/potassium chloride (KCl) mixture increased by three orders of magnitude as compared to HPMC solution at temperatures below apparent gelation temperature. The gel elastic modulus of the solution blend of HPMC/KCG/salt mixture decreased in the order of KCl > NaCl > CaCl2. Thermal analysis revealed a linear relationship between the depression of melting temperature and the salt concentrations, which is independent of KCG. The free water content computed by enthalpy data showed that free water content decreased with increasing salt concentrations. The secondary peak which typically associated with bound water appeared in the mixture of HPMC and KCG in the presence of KCl. As the concentrations of KCl salt increased, the bound water peak also amplified and lifted to a higher temperature.